Development of Conductor-Backed Coplanar Waveguide (CBCWG) Moisture Sensors - Teoh, Lay Hua (1997)
Conductor-backed coplanar waveguide (CBCWG)l moisture sensor has been developed for a quick and accurate determination of moisture content in fresh mesocarp of the oil palm ftuits and cocoa beans. The sensor consists of three parts i.e, the coupling system representing the 1ranSition between coaxia11ine to the CBCWG, the 2-layer structure of the CBCWG and sensing area. Previous wade done shows a close relationship between the oil content and moisture content in the oil palm mesocarp during fruit development The quality of cocoa beaus were also affected by the moisture content in the beans. Thus, by measuring the moisture content in the oil pahn mesocarp and cocoa beans, the quality of the oil palm fruit and the cocoa beans can be obtained indirectly. A functional relationship has been developed between scattering parameter 821 of the sensor and moisture content of the sample. The reflection and transmission phenomena in the sensor structure can be represented by a signal flow graph and can be simplified by using Mason's non-touching loop roles. The calculation of S21 is based on the quasi-transverse electtomagnetic mode approxima1ion. Based on the theoretical analysis, computer programmes written in FORTRAN programming language were developed to do the calculations of the attenuation. A total of four different sensors were developed in order to find out the effect of different gap between the conducting S1rip and upper ground plane and protective layers on the attenuation values. It is found that the big gap sensor gives a better sensitivity as compared to the small gap sensor. This effect is probably due to the field density in the big gap sensor is much higher than the small gap sensor. The sensitivity of the sensor is also drastically affected by the thickness of the protective layer. This is due to the decreasing of the interaction between the field and the sample as the thickness of the protective layer increases. A comparison between the theoretical and experimental results for the oil palm mesocatp was done. A close agreement has been found. The difference in value ranges from only 1-4dB. The fine relationship between the attenuation and moisture content for this kind of sensor gives the possibility for the development of a compact and portable microwave instrument for assessing the quality of cocoa and oil palm fruits that are sent to the factory.